(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Biometrics is attracting more and more attention as businesses look for more secure authentication techniques for e-commerce, user access, and other security applications. With the primary goal of serving as an introduction to this topic, this paper provides an outline of major biometric technologies. Compared to conventional ways of recognizing persons, biometrics can provide more security and ease. Therefore, this paper aims to provide a fundamental behind the topic and further challenges associated with the use of biometrics. It has been revealed that biometric security is a rapidly expanding area of study that deals with using the body’s unique identifiers for access management and control. As Biometric technologies are gaining traction, more and more security, ethical and privacy concerns are emerging that need to be addressed for harnessing the full potential of biometric technologies.